Third molars in the establishment of adult status - a case report - Nambiar, P.; Yaacob, H.; Menon, R. (1996)
Teeth are the most durable structures in the human body. The timing and sequence of their development, as contained in dental development charts, have been used as valid criteria for age determination. The third molars however are the last teeth to erupt and are regarded as the most variable in the dentition. Age estimation in a legal context, using developing third molars must be carefully applied otherwise justice may miscarry. A case of wrongful use of the technique is presented here.